Geovisión: una infraestructura abierta de datos espaciales - Campos-Vargas, Carlos A. (2015)
Costa Rican State University of Distance Education (UNED) has recently assumed the use of geospatial information as a good practice for its research activities. Therefore the university implemented an Open Spatial Data Infrastructure (Open SDI) known as Geovision. Its development process and corresponding results are presented, from the initial user group developing stages to the current publication of geospatial web services. Geovision conceives itself as an open SDI in two specific aspects, first the service is available to users without regard of the institutions they belong to, and second, for its use of open source software and open protocols. This SDI enables all the tools needed for publishing and sharing geospatial information in formats suited to both experienced and novel users.